Corpus Alienum Conjunctiva Bulbi with Subconjunctival Bleeding Due to Nail Trauma: The Importance of Eye Protection - Dewanti Widya Astari; Geriska Ayu Prihayanti; Yusi Entin Nurhayati (CV. Global Health Science Group, 2025)
Ocular trauma is a significant cause of preventable blindness, with home renovation activities being common contributing factors. This case emphasizes the critical role of comprehensive nursing care in managing corpus alienum conjunctiva bulbi with subconjunctival bleeding. To describe ocular trauma caused by nail fragment resulting in corpus alienum conjunctiva bulbi with subconjunctival bleeding, emphasizing evidence-based nursing interventions and eye protection importance. A 41-year-old male construction worker presented with left eye redness, pain, and foreign body sensation following nail trauma during home renovation. Clinical examination revealed a 2mm iron fragment embedded in the nasal bulbar conjunctiva with extensive subconjunctival bleeding. Data were collected through comprehensive nursing assessment including vital signs monitoring, pain evaluation (numeric rating scale 7/10), visual acuity testing (6/18 improving to 6/12 with pinhole), and anterior segment photography. Data analysis involved reviewing clinical findings, examining sequential photographic evidence, and evaluating patient responses to interventions. The patient underwent successful foreign body extraction under topical anesthesia with systematic nursing care management. Complete foreign body removal was achieved without complications. Pain reduced to 2/10 within 24 hours. The patient demonstrated proper medication administration techniques and understanding of home care instructions. Subconjunctival hemorrhage resolved within 10 days with visual acuity returning to baseline (6/6). No adverse events occurred at follow-up. This case demonstrates nursing care's essential role in optimizing ocular trauma outcomes through systematic assessment, evidence-based interventions, patient education, and continuity of care. The case reinforces eye protection's critical importance during renovation activities and comprehensive nursing care's contribution to successful outcomes.